Design of a Website-Based Thesis Repository Information System (Case Study: Faculty of System Engineering, Sumbawa University of Technology) - Sukarti (Management of Information System Journal, 2025)
The rapid development of information and communication technology (ICT) encourages higher education institutions to manage academic documents digitally and in an integrated manner. The Faculty of Engineering Systems at Universitas Teknologi Sumbawa (UTS) faces challenges in managing thesis repositories that are still conducted manually, leading to limited access, document loss risks, and inefficient administration. This study aims to design and develop a web-based thesis repository information system using the prototyping method involving active user participation. The system provides features for uploading, verifying, and searching theses with multi-role access (admin, lecturers, students). The prototyping method allows iterative evaluation and refinement of the system based on user feedback. The implementation is expected to improve document management efficiency, accelerate information access, and support the digitalization of academic services within the faculty. The results indicate that this approach effectively addresses thesis management challenges and significantly enhances academic service quality.